APPLICATION GEOGRAPHIC INFORMATION SYSTEM (GIS) ANDREMOTE SENSING TO ASSESS LANDCOVER TRANSITION IN DIOXIN IMPACTED AREA (TA BHINH, CHA VAL AND LA DE, NAM GIANG DISTRICT, QUANG NAM PROVINCE) FOR BIODIVERSITY CONSERVATION - Cảnh, Lê Xuân; Thư, Đỗ Hữu; Phương, Đặng Huy; Quỳnh, Hà Quý (Vietnam Journal of Science and Technology, 2012)
SUMMARYLand cover plays an importance role for creating the habitats and biodiversity conservation. This article show result of using GISand remote sensing to assess land cover transition in Ta Bhinh, Cha Val, and La De commune,Nam Giang District, Quang Nam province. The input data included: Remote sensing data, field data collection and topographic map. The land cover in area included: 1) Tropical evergreen forest below 800 m; 2). Sub-tropical evergreen forest above 800 m: 3).  Degraded Sub-tropical evergreen forest above 800 m; 4) Degraded tropical evergreen forest  below 800 m; 4 Settlement and 5) water body. The biodiversity decrease from type 1,2 to type 3,4. The composition of the humus decrease from 4% in type 1 to 2% in type 4. The humidity balance is decreased from type 1 to type 4. The fauna in the area is decreased in species composition, number of individual, density, biomass from type 1 to type 4. The vegetation change from topical evergreen in type 1,2 to degrade evergreen forest in type 3, and to scrub, grassland or bare land in type 4. The land cover in the area transits in both of structure and square area. The type 2 and type 5 had widest radian during 1975-2008. The grasslandand scrub created by the dioxin impacted during American war had especially generating whichunlike the blank area. The result of using Remote sensing and GIS technology for study land cover transition is objective, clearly displayed. This result will benefit not only land cover change, but also the suite of associated endemic species in the enclosedhabitat.